Resolution of oncogene-induced senescence markers in HPV-infected cervical cancer tissue - Ashraf I. Khasawneh; Sofian Al Shboul; Nisreen Himsawi; Amani Al Rousan; Nisreen Abu Shahin; Mohammed El-Sadoni; Ahmad Alhesa; Ala’ Abu Ghalioun; Suzan Khawaldeh; Bayan Shawish; Salem Abu Mahfouz; Mais Al-Shayeb; et al. (BMC Cancer)
Abstract Background Oncogene-Induced Senescence (OIS) is a form of senescence that occurs as a consequence of oncogenic overstimulation and possibly infection by oncogenic viruses. Whether senescence plays a role in the pathogenesis of cervical cancer (CC) is not well understood. Moreover, whether cervical epithelial cells that are part of the premalignant cervical intraepithelial neoplasia (CIN), exhibit markers of OIS in Human Papillomavirus (HPV)-infected tissue, has not been investigated. Methods We utilized a set of patient-derived premalignant and malignant tissue samples to investigate the protein (Ki67 and Lamin B1) and gene (TP53, IL1A, CCL2, and MMP9) expression of several OIS-associated biomarkers using immunohistochemistry (IHC) and qRT-PCR, respectively. Furthermore, we characterized the HPV status of all tissue samples. Results Most of the CC samples (34/37) were positive for HPV, mainly HPV-16 which was observed in 62.2% of the CC samples. Among CINs, HPV infection was found in 60.2% of the 32 samples with HPV-16 as the dominant genotype in 58.5% of the CINs. IHC analysis revealed a significant increase in the expression levels of both Ki67 and Lamin B1 proteins in CC tissue compared to CIN. On average, 93% of tumor cells were positive for Ki67 in comparison to only 25% of premalignant cells in CIN samples. Similarly, Lamin B1 expression was observed in 89% of tumor cells in malignant tissue on average, compared to 60% in CIN samples. Importantly, Lamin B1 expression was elevated in nonmalignant cervical tissue suggesting that its downregulation is more predominant in the premalignant state. Furthermore, RT-PCR revealed a significant decrease in the expression of TP53, IL1a, CCL2, and MMP9 markers in CC samples compared to CINs. Specifically, 84% of CC samples showed reduced TP53 expression, 90% showed reduced IL1a expression, 74% showed reduced CCL2 expression, and 76% showed reduced MMP9 expression when compared with their premalignant baseline. Infection of HPV was confirmed in 61% of the tumor tissues while only 25% of the CINs were positive for HPV. Conclusion This work shall provide an opportunity to further examine the role of OIS in the process of HPV-driven CC development.